Measles in Czech population with varying vaccination rates in 2018-2019: clinical and laboratory differences between vaccinated and unvaccinated individuals and their relevance to clinical practice - Smíšková, Dita; Janovic, Simona; Kadeřávková, Pavlína; Nováková, Ludmila; Blechová, Zuzana; Malý, Marek; Limberková, Radomíra (Infectious diseases (London, England), 2024)
BACKGROUND AND OBJECTIVES: In a highly vaccinated population, an increasing number of previously vaccinated measles cases can be expected. The aim of this study was to assess the effect of vaccination on the clinical course and immune response in relation to the current measles case definition. METHODS: The presence of fever, catarrhal symptoms, exanthema and complications, and specific IgM and IgG positivity were assessed in all 230 patients and compared in 193 patients with known vaccination status, divided into measles-containing vaccine (MCV) groups: MCV0 (85 patients), MCV1 (25 patients) and MCV2 (83 patients). RESULTS: Statistically significant differences between groups were found for catarrhal symptoms. Conjunctivitis and rhinitis were significantly less frequent in the MCV2 group (47% and 54%) compared to MCV0 (80% and 80%), p < 0.001 and p = 0.002 respectively. Typical exanthema was present in 74 (87%) MCV0 and 56 (67%) MCV2 patients, p = 0.005. Complications were most common in the MCV0 group (29%). ECDC clinical case criteria were met in 81 (95%) MCV0, 18 (72%) MCV1 and 59 (71%) MCV2 patients, p < 0.001. IgM were positive in 64 (83%) MCV0, 14 (74%) MCV1 and 36 (67%) MCV2 patients, differences were not statistically significant. There were highly significant differences in IgG between MCV0 and both vaccinated groups (p < 0.001). CONCLUSIONS: A redefinition of the clinical case classification is essential to better capture modified measles and to raise awareness among healthcare workers of the differences in measles in vaccinated patients.
Keywords: Young Adult; Immunoglobulin G; Male; Measles; protilátky virové; Child, Preschool; Unvaccinated Persons; Immunoglobulin M; mladý dospělý; Adolescent; imunoglobulin M; Infant; Česká republika; Child; dítě; Adult; imunoglobulin G; dospělí; mužské pohlaví; spalničková vakcína; clinical case definition; mladiství; vakcinace; Czech Republic; předškolní dítě; lidé; vaccination; ženské pohlaví; neočkované osoby; Humans; Measles Vaccine; kojenec; Vaccination; modified disease; serology; spalničky; Antibodies, Viral; Female